2022
DOI: 10.3390/en15062021
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Sub-23 nm Particles Emitted from PFI/DI SI Engine Fueled with Oxygenated Fuels: A Comparison between Conventional and Novel Methodologies

Abstract: This study focuses on the measurement of sub-23 nm particles emitted from a small DI/PFI spark ignition engine through conventional techniques and innovative systems. Measurements were performed with well-known systems, such as the EEPS coupled to a PMP-compliant sample conditioning device. Moreover, a novel instrument developed within the European project Sureal-23, the advanced HM-DMA, capable of operating with a simplified conditioning setup was used. The engine was fueled with ethanol, both pure and in ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For example, for diesel vehicles, 23 nm was considered the appropriate size, i.e., the smallest primary soot spherule [36]. Many studies, however, found particles below 23 nm for gasoline direct injection (GDI), port-fuel injection (PFI) vehicles, motorcycles, compressed natural gas (CNG) vehicles, and even diesel vehicle (e.g., urea particles) [37][38][39][40]. Furthermore, determination of the technical requirements of the instruments for on-road testing, i.e., portable emission measurement systems (PEMSs), needs an appropriate size range due to its impact to measurement uncertainty and, thus, on the definition of conformity factors [41].…”
Section: Introductionmentioning
confidence: 99%
“…For example, for diesel vehicles, 23 nm was considered the appropriate size, i.e., the smallest primary soot spherule [36]. Many studies, however, found particles below 23 nm for gasoline direct injection (GDI), port-fuel injection (PFI) vehicles, motorcycles, compressed natural gas (CNG) vehicles, and even diesel vehicle (e.g., urea particles) [37][38][39][40]. Furthermore, determination of the technical requirements of the instruments for on-road testing, i.e., portable emission measurement systems (PEMSs), needs an appropriate size range due to its impact to measurement uncertainty and, thus, on the definition of conformity factors [41].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, compression ignition engines emit higher amount of exhaust gases such as nitrogen oxides (NOx), soot and particulate matter (PM) emissions. On the other hand, gasoline engines have advantages in view of the lower exhaust emissions, quieter operation and cheaper for initial cost [1][2][3][4][5][6][7][8][9]. However, gasoline engines need to be operated at near stoichiometric air/fuel ratios due to usage of catalytic converter.…”
Section: Introductionmentioning
confidence: 99%
“…Because compression ratio can not be increased due to auto ignition characteristics of gasoline. At this point, fuel addition into gasoline is seen to be attractive approach in order to increase the engine performance and thermal efficiency [2][3][4][5][6][7][8][9][10]. Alcohol based alternative fuels have attracted great attention in spark ignition engines due to higher octane number and oxygen content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation